Sosialisasi Penggunaan Airbag Untuk Peluncuran Kapal Kayu di Kelurahan Galesong Kota, Kecamatan Galesong, Kabupaten Takalar - Ganding Sitepu; Lukman Bochary; Mohammad Rizal Firmansyah; Wihdat Djafar; Rosmani .; Suandar Baso; Indrawansyah .; Editya . (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
One of the centers for traditional wooden boat construction in South Sulawesi is Galesong District, Takalar Regency, South Sulawesi. Generally, wooden boats constructed by craftsmen in this area are for fishing. Craftsmen's skills in building the boat were acquired from their predecessors. However, the craftsmen still faced some problems during the boat construction work. One of the problems is related to launching the boat into the water, which is still conducted traditionally using logs and sandbags. The solution is to propose the use of airbags to launch ships. Airbags have been used to launch steel ships but relatively not for wooden boats. Hence, this activity aims to introduce the use of airbags to launch the boat. The target for the introduction is a group of wooden boat craftsmen, "Patorani," in Galesong District, Takalar Regency. Before and after the activity, achievements are evaluated by identifying the perceptions and views of craftsmen regarding the airbags. The activity is conducted through socialization and explanations of airbags with visualization. The result shows that almost 90% of the craftsmen had never heard of airbags before and were unsure that airbags could be used to launch the boat. However, after the activity, most craftsmen can be convinced that airbags can solve their boat launching problems. Only one participant out of 15 still had doubts about the use of airbags for boat launching. The rest of the participants were even ready to use the airbags to launch their boats.